Ultraviolet curable acrylic copolymer based electrolytes for dye-sensitized solar cell application / Nurul Akmaliah Dzulkurnain - Nurul Akmaliah , Dzulkurnain (2016)
New copolymers using methyl methacrylate (MMA) and ethyl methacrylate (EMA) monomers were randomly copolymerized via free-radical bulk polymerization method towards development as solid electrolyte in dye sensitized solar cell (DSSC). In this study, copolymer of 90MMA:10EMA showed the most promising characteristics to be used as host in polymer electrolytes due to its smooth cross sectional surface, lowest resistivity, low molecular weight, and glass transition temperature. Therefore, 90MMA:10EMA was incorporated with different weight ratios of lithium iodide and sodium iodide. The complexation between salts and copolymer host has been investigated using Fourier transform infrared spectroscopy. The ionic conductivity and thermal stability of the electrolytes were measured using impedance spectroscopy and differential scanning calorimetry, respectively. The highest ionic conductivities found for lithium iodide and sodium iodide systems were at 20 wt% with the value of 1.3 × 10-6 S cm-1 and 5.19 × 10−6 S·cm−1 respectively. The DSSCs employing the copolymer electrolytes with suitable working and counter electrodes were tested under AM 1.5 illumination at a light intensity of 100 mW·cm−2. The DSSC exhibited photo-conversion efficiency of 0.45% for electrolytes containing lithium iodide and 0.62% for that containing sodium iodide. Furthermore, lithium and sodium iodide based polymer systems were added with 1-Methyl 3-propyl imidazolium iodide ionic liquid to study the characteristics of the electrolytes and to enhance the photo conversion efficiency of DSSCs. The electrolyte for both systems exhibited highest ionic conductivity at 6 wt% of ionic liquid with the value of 8.93 × 10-8 S cm-1 for lithium based and 4.43 × 10-5 S cm-1 for sodium based. The photo-conversion efficiency of DSSC employing ionic liquid based electrolytes demonstrated an increment of 1.19% for copolymer-lithium iodide-ionic liquid and 1.05% for copolymer-sodium iodide-ionic liquid. These performances strongly suggested that the polymer electrolytes are promising electrolytes for DSSC application.